Conversational Incongruity and Humor in Facebook Memes: A Pragmatic Study of Online Language Use - Hasbiya Miryami Jundiyaturrahman; Hilmi Akmal; M Agus Suriadi; Sholikatus Sa’diyah (Journal of Pragmatics Research, 2025)
Memes serve not only as entertainment but also as linguistic texts that reflect how humor is pragmatically constructed. This study examines how humor is generated through the creation of implicatures in conversational memes by analyzing the flouting of Grice’s Cooperative Principles, particularly the maxim of relation. Qualitative research is conducted through the analysis of selected memes from the English Memes Facebook page from 2023 to 2024. The research applies Gricean pragmatics alongside Ritchie’s Incongruity Theory to interpret how conversational expectations are deliberately disrupted to produce humorous effects. Findings reveal that flouting the maxim of relation is the most prevalent, followed by quality and quantity, indicating that intentional irrelevance effectively creates incongruity and implicature. By extending Grice’s framework into digital discourse, this study contributes to the broader field of digital humanities, offering insight into the linguistic mechanisms underlying humor in online meme culture.